Cultural resilience of the Kajang Dalam communities: Customary law, rituals, and Kamase-masea values in facing change - Arisnawawi, Arisnawawi; Aksyar , Mohammad (Jurnal Sosiologi Dialektika, 2026)
The Kajang indigenous people in Bulukumba Regency, are known for their principles of Kamase-masea (simplicity) and adherence to customary law and the teachings of Pasang ri Kajang. This article analyzes how the Kajang people’s cultural resilience is built through customary law, rituals, and Kamase-masea values in the face of social change and modern crises, including the COVID-19 pandemic and the pressures of modernization. The research used a qualitative approach through in-depth interviews. The results show that customary law functions as an instrument for conflict resolution and a deterrent against external intervention. Customary rituals play a crucial role in strengthening social solidarity and maintaining community cohesion. Kamase-masea values serve as the foundation for a simple lifestyle that is adaptive to crisis situations. This study concludes and confirms that the cultural resilience of the Kajang people is not a form of absolute rejection of modernity, but rather a strategy to slow the pace of change to prevent the erosion of fundamental customary values. These findings make an important contribution to the sociology of disaster studies by demonstrating that customary law, ritual, and the values of a simple lifestyle can serve as community resilience mechanisms in the face of the pressures of change.